2021
DOI: 10.1101/2021.02.26.433025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Choice of method of place cell classification determines the population of cells identified

Abstract: Place cells, spatially responsive hippocampal cells, provide the neural substrate supporting navigation and spatial memory. Historically most studies of these neurons have used electrophysiological recordings from implanted electrodes but optical methods, measuring intracellular calcium, are becoming increasingly common. Several methods have been proposed as a means to identify place cells based on their calcium activity but there is no common standard and it is unclear how reliable different approaches are. H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Computing statistics for average JS divergence between place fields, percentiles exceeding 0.95 and information score thresholds in range ½0:8; 1:5 result in statistically lower JS divergence between place fields exclusively identified by SCOUT compared with those identified exclusively by cellReg (min p = 0.0079, max p = 0.0488, linear mixed effects model with fixed cell-tracking method grouped by recording, Figure 6B). This range of values matches that of a previous study (Grijseels et al, 2021) that suggests a percentile threshold of 0.95-0.99 of place cells, while experimentation showed that neurons with information score threshold exceeding 1.0 showed strong spatially localized firing activity.…”
Section: Testing Performance Via Place Cell Stability Analysissupporting
confidence: 90%
“…Computing statistics for average JS divergence between place fields, percentiles exceeding 0.95 and information score thresholds in range ½0:8; 1:5 result in statistically lower JS divergence between place fields exclusively identified by SCOUT compared with those identified exclusively by cellReg (min p = 0.0079, max p = 0.0488, linear mixed effects model with fixed cell-tracking method grouped by recording, Figure 6B). This range of values matches that of a previous study (Grijseels et al, 2021) that suggests a percentile threshold of 0.95-0.99 of place cells, while experimentation showed that neurons with information score threshold exceeding 1.0 showed strong spatially localized firing activity.…”
Section: Testing Performance Via Place Cell Stability Analysissupporting
confidence: 90%
“…As such, we offer examples of the EMD's increased spatial sensitivity using activity maps from recorded cells. We offer a combination of individual examples that depict specific cell types, or representative maps, as well as an open-source place cell dataset from the hippocampus (HPC; Grijseels D. et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Place cells from hippocampal CA1 two-photon microscopy recordings in mice running across a virtual linear track were obtained from a published dataset (Grijseels D. et al, 2021 ). Deconvolved spike trains from Suite2P outputs were used directly as cumulative spike counts and converted to 1D firing rates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Net haemodynamic measurements were recorded using the Oxy-CBF probe and individual vessels and neurons were imaged using 2 photon microscopy. Figure adapted from Grijseels et al (2021); (D) Example output from a capillary line scan after preprocessing (left) and the same image binarised (right) for haematocrit measurements. No genotype differences were found in RBCV (E) or in haematocrit (G) measures but a trend towards increased RBCV coefficient of variation (CV) was observed in APOE4 animals (F) .…”
Section: Resultsmentioning
confidence: 99%